Domestic violence assault during the first year of the COVID-19 pandemic: a longitudinal community study - Yasmin B. Kofman; Cassidy C. D. Weiss; Ilona S. Yim (BMC, 2023)
Abstract Background The consequences of the COVID-19 pandemic have been far-reaching, disproportionately impacting vulnerable populations. Of particular concern is the impact on individuals experiencing domestic violence (DV), an urgent public health issue. There have been numerous reports of pandemic-related surges in DV, and it has been speculated that prolonged periods of state-mandated isolation may be the source of these surges. The current study utilized publicly available records to examine fluctuations in DV coinciding with COVID-19 lockdown restrictions in a diverse metropolitan county. Methods Data were extracted from local police blotters and mapping engines in Orange County, California (United States), documenting police-reported DV assault. All incidents were coded for time to examine the time course of DV among other types of assault, allowing for a longitudinal view of incidents over a 66-week window. Changepoint analyses were used to determine whether and when DV assaults changed when mapped with coinciding tightening or loosening of restrictions county-wide. Piecewise regression analyses evaluated whether any detected fluctuations were statistically meaningful. Results In Santa Ana, rates saw a small but significant spike in the week following the first major lockdown in March 2020 (b = .04, SE = .02, t = 2.37, p = .01), remaining stable at this higher level thereafter (b = -.003, SE = .003, t = -1.29, p = .20). In Anaheim, no meaningful change in DV assault rates was observed at any time interval. Conclusion Results suggest that surges in DV vary between communities and that systemic issues may set the stage for the surge of an already endemic problem.